2006
DOI: 10.1080/07352680600794232
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Strategies for Regulation of Nitrification in Agricultural Systems—Challenges and Opportunities

Abstract: Nitrification, a microbial process, is a key component and integral part of the nitrogen (N) cycle. Soil N is in a constant state of flux, moving and changing chemical forms. During nitrification, a relatively immobile N-form (NH + 4) is converted into highly mobile nitrate-N (NO − 3). The nitrate formed is susceptible to losses via leaching and conversion to gaseous forms via denitrification. Often less than 30% of the applied N fertilizer is recovered in intensive agricultural systems, largely due to losses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
347
2
21

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 447 publications
(375 citation statements)
references
References 292 publications
(434 reference statements)
5
347
2
21
Order By: Relevance
“…Fertilizer-N consumption is expected to reach 200 Tg⅐y Ϫ1 by 2025 from the present 150 Tg⅐y Ϫ1 (2,40,41). Environmental damage could result, given the pervasive inefficiencies in N use (Ͻ40% of applied N is recovered by most field crops) (2, 42), due largely to nitrification and its associated processes (1,13). The economic implications of this ''wasted N'' can be enormous; they are currently estimated as US$ 17 billion from cereal production systems alone (13,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilizer-N consumption is expected to reach 200 Tg⅐y Ϫ1 by 2025 from the present 150 Tg⅐y Ϫ1 (2,40,41). Environmental damage could result, given the pervasive inefficiencies in N use (Ͻ40% of applied N is recovered by most field crops) (2, 42), due largely to nitrification and its associated processes (1,13). The economic implications of this ''wasted N'' can be enormous; they are currently estimated as US$ 17 billion from cereal production systems alone (13,43).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrification is low in some forest and grassland soils (13)(14)(15)(16)(17). Since the early 1960s, some tropical grasses have been suspected of having the capacity to inhibit nitrification (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Interestingly, although leguminous crops fix N (so do not require additional N fertiliser) leguminous pastures can also give rise to N leaching, thus permitting N 2 O production (7) . Realistic targets for environmental improvement include an increased use of precision agricultural techniques for fertiliser application and increasing N use efficiency (the ability of plants to take up and sequester N) of crop plants (7) . A further opportunity is to exploit the natural presence of N-fixing endophytic bacteria on the roots of non-leguminous crop plants, including grasses (22)(23)(24) , the success of which will enable decreased requirement to add N fertilisers to land for forage production.…”
Section: Ruminants As a Source Of Environmental Pollutantsmentioning
confidence: 99%
“…Controlling the process of nitrification through inhibition or suppression of nitrifiers in soil is perhaps one of the most effective strategies to reduce N losses by NO 3 -leaching and by gaseous N emissions that occur in nitrification (Rodgers 1986;Prasad and Power 1995;Subbarao et al 2006b). Field evaluations suggested that if nitrification rates are reduced in agricultural systems, plants have more time to take up available N, thereby improving N recovery and uptake and reducing NO 3 -leaching and associated off farm environmental impacts (Rodgers 1986;Subbarao et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Field evaluations suggested that if nitrification rates are reduced in agricultural systems, plants have more time to take up available N, thereby improving N recovery and uptake and reducing NO 3 -leaching and associated off farm environmental impacts (Rodgers 1986;Subbarao et al 2006b). …”
Section: Introductionmentioning
confidence: 99%